The role and effect of service network actors on continuous service innovation: A case study in the business-to-business health sector - Lambourdiere, Edwina (2014)
Purpose – The purpose of this dissertation is to investigate service innovation in networks and to unravel how and why external network actors contribute to the innovation of services of an innovating firm in the healthcare business-to-business industry, as it was argued that it could be influenced by the context. Additionally, this study explores the consequences of such involvement of the external actors.